Ready for a Fair Deal: Librarian and Archivist Leadership During a Canadian Faculty Association Strike - Dingwall, Orvie; Ford, Lyle; Warren, Ruby (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire, 2022)
Canadian academic libraries are unionized environments, requiring collective organization and action to address labour conditions and contract negotiations. The University of Manitoba Faculty Association (UMFA) has 1264 members, including 52 archivists and librarians, and in 2021 resolved the longest strike in association history. The newly ratified agreement contained major gains to advance pay equity within the union, and the strike itself maintained UMFA historic high levels of participation and member engagement, in part due to the significant contributions of librarians and archivists. In this paper, three librarians who held distinct positions of leadership within UMFA, particularly during its 2021 strike, examine the unique strengths and difficulties of librarians and archivists working within a broader faculty union to make change. Relying on core competencies of librarianship, such as collaboration, consultation, communication, and leadership, the authors collectively and successfully filled central roles in the strategic direction, organizational foundation, and on-the-ground mobilization of the strike effort. The historical context for the labour climate and organizing history at the University of Manitoba is examined and demonstrates that core competencies of librarians and archivists are valuable and imperative skills in faculty union organizing. Librarians and archivists can use this narrative to inform the development of their own activism within their unions and workplaces, and to examine how their own skills may help enhance and improve their working conditions.